Faktor-faktor gaya hidup yang berpengaruh terhadap peningkatan risiko sindrom metabolik di kalangan mahasiswa - Wahyuddin, Ahmad; Putri, Try Kartika Eka (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2025)
Background: Metabolic syndrome is increasingly common among young people, including college students, as a result of modern lifestyle changes. Shifts in eating behavior toward high-fat and high-sugar foods, low physical activity, and high academic pressure lead to metabolic imbalance. Purpose: To analyze lifestyle factors contributing to the increased risk of metabolic syndrome among college students. Method: This was a descriptive qualitative study utilizing in-depth interviews and focus group discussions (FGDs) with students from various study programs. Data were analyzed thematically, emphasizing health behavior patterns, eating habits, physical activity, and students' perceptions of metabolic syndrome prevention efforts. Results: Three main factors are indicated to interact and influence the risk of metabolic syndrome: an unbalanced lifestyle, low physical activity and a predominantly sedentary lifestyle, and low preventive awareness and minimal campus institutional support, which undermine the implementation of healthy lifestyle behaviors. Conclusion: Preventing metabolic syndrome in college students requires a holistic approach based on a healthy campus (Healthy Campus Framework) that includes the integration of health education, increased physical activity, and strengthening institutional policies that support sustainable healthy lifestyle behaviors.   Keywords: College Students; Metabolic Syndrome; Physical Activity; Prevention; Sedentary Lifestyle.   Pendahuluan: Sindrom metabolik semakin umum di kalangan anak muda termasuk mahasiswa, sebagai akibat dari perubahan gaya hidup modern. Pergeseran perilaku makan ke arah makanan tinggi lemak dan tinggi gula, aktivitas fisik yang rendah, dan tekanan akademik yang tinggi menyebabkan ketidakseimbangan metabolik. Tujuan: Untuk menganalisis faktor-faktor gaya hidup yang berkontribusi terhadap peningkatan risiko sindrom metabolik di kalangan mahasiswa. Metode: Penelitian kualitatif deskriptif dengan memanfaatkan wawancara mendalam dan diskusi kelompok terfokus (FGD) kepada mahasiswa dari berbagai program studi. Data dianalisis secara tematik, menekankan pola perilaku kesehatan, kebiasaan makan, aktivitas fisik, dan persepsi mahasiswa terhadap upaya pencegahan sindrom metabolik. Hasil: Terindikasi ada tiga faktor utama yang berinteraksi dan memengaruhi risiko sindrom metabolik, yaitu gaya hidup tidak seimbang, aktivitas fisik yang rendah dan gaya hidup yang didominasi sedenter, dan kesadaran preventif yang rendah dan minimnya dukungan institusi kampus yang melemahkan penerapan perilaku hidup sehat. Simpulan: Pencegahan sindrom metabolik pada mahasiswa memerlukan pendekatan holistik berbasis kampus sehat (Healthy Campus Framework) yang mencakup integrasi edukasi kesehatan, peningkatan aktivitas fisik, dan penguatan kebijakan institusi yang mendukung perilaku hidup sehat berkelanjutan.   Kata Kunci: Aktivitas Fisik; Gaya Hidup Sedentary; Mahasiswa; Pencegahan; Sindrom Metabolik